In Vitro And In Vivo Studies Of Chicken Gut To Produce Chicken Probiotics By Isolated Microbes From Local Fermented Foods - Jakera, Shakera (2022)
Globally, the use of poultry feed is increasing because of the consistent needs and production of poultry meat and eggs. Egg and meat provide us proteins, iodine, iron, zinc, minerals, and vitamins. Several chemically synthesized antimicrobial agents and antibiotics are currently used in poultry feed as growth promoters and to improve performance. These antibiotic residues will remain in chicken meat, bones, and organs and may eventually have a negative impact on human health. Probiotics are one solution, however not all isolated and produced probiotics are useful for poultry and act well. Fermented soy cake and shrimp paste was used in this study to isolate potential chicken probiotic such as bacteria and yeast. For this study, including the isolation of microorganisms from fermented shrimp paste and soya cake, nine yeast and ten bacteria were selected as test sample. After isolating the organisms, for each microorganism, an in vitro analysis was conducted while maintaining full chicken gut parameters, which includes 37°c temperature, anaerobic condition and seven different pH (2.5, 3.5, 5, 6.5, 7, 7.5, and 8). Following in vitro testing, SB3, SB5, and SB10 strains outgrew other strains in terms of growth rate and biomass production across all pH ranges. At all pH levels, SY1, SY2, SY3, SY4, and SY8 grew higher and yielded more.